Long-Read Draft Genome Sequences of Two Fusarium oxysporum f. sp. cubense Isolates from Banana (Musa spp.) - Jiaman Sun; Jinzhong Zhang; Donald M. Gardiner; Peter van Dam; Gang Fu; Brett J. Ferguson; Elizabeth A. B. Aitken; Andrew Chen (Journal of Fungi, 2025)
Fusarium oxysporum f. sp. cubense (Foc) causes Fusarium wilt, a devastating epidemic disease that has caused widespread damage to banana crops worldwide. We report the draft genomes of Foc race 1 (16117) and Foc tropical race 4 (Fusarium odoratissimum) (CNSD1) isolates from China, assembled using PacBio HiFi sequencing reads, with functional annotation performed. The strains group in distinct lineages within the Fusarium oxysporum species complex. This genetic resource will contribute towards understanding the pathogenicity and evolutionary dynamics of Foc populations in banana-growing regions around the world.